The contributions of forestry sub sector to economic development in Nigeria: A case study of Ekiti state (2006)
One of the major problems facing forestry development in Nigeria is the under-valuation of forestry contribution to national economic development. This study therefore examines forestry contribution to the economic development of Ekiti state from 1997-2006. Primary data were collected with the use of well structured questionnaires and interviews with top management staff and divisional forest officers of the State, while secondary data were gathered from classified documents of the State Forestry Department (SFD).. The study observes that sawmills and timber contracting are the only forest based enterprises that are registered with the SFD. The 153 sawmills in the state employ about 2,085 people while there are 179 timber contractors. The results reveal that forestry contributed a total sum of N333,950,675 to the state's Internally Generated Revenue (IGR), while the state spent only N21.7 million for forestry development over the ten year period of study. The percentage contribution of forestry revenue to the state's total IGR ranges between 4 and 26% in 1997 and 2006 respectively. The programmes used for the development of forest resources inn the state include: Timber Development Law, Taungya System, Forestry Trust Fund, Ecological Project and Woodlot Development Project. Forestry has great potential to contribute to economic development of Ekiti State; however, inadequate forestry expenditure is a major constraint to the realisation of this potential. Forest managers will therefore have to evolve strategies to elicit greater commitment from the state government to fund forestry projects.